Bringing Technology to English Language Learning: Making It Work - Frank Otto (Asociación Colombiana de Profesores de Ingles, 2016)
Interactive Multimedia (IMM) has been accepted as an exemplary application of modern technology that is used to teach and learn foreign languages more effectively, especially in ELT programs. We discuss the development and application of IMM and its principal features in terms of the positive impact that has on improving the learning environment in foreign language education. It has achieved incredible success because it has increased test results among learners and satisfaction among teachers and their students.